Developing a Bilingual Guidebook of Panji Museum - Gusti Ayu (UPT P2M Politeknik Negeri Malang, 2022)
The Panji Museum, located in Malang, East Java, is an educational and cultural institution showcasing the story of Panji, historical relics, and the traditional culture of the Javanese people. However, the museum faces significant challenges in providing clear and comprehensive information to its visitors due to inadequate descriptive materials and supporting facilities. This lack of accessible and accurate information affects the visitor experience, particularly for international tourists. To address this issue, the present study aimed to develop a bilingual (Indonesian-English) guidebook for the Panji Museum, with the goal of enhancing information delivery and accessibility for both domestic and international audiences. This research adopted a design and development methodology, consisting of five stages: analysis, design, development, expert validation, and evaluation. Data collection instruments included questionnaires and interviews conducted with both domestic and international visitors. The primary outcome was a bilingual guidebook featuring comprehensive information about the Panji Museum, including an overview of its history, the story of Panji, contributions of Panji researchers, and detailed descriptions of 37 curated collections. Additionally, the guidebook includes visual aids, such as photographs and a floor plan, as well as practical information about museum facilities, contact details, and social media presence. Evaluation results indicate that the bilingual guidebook significantly improves visitors’ understanding and engagement with the museum’s collections. It effectively bridges the language barrier and enhances the overall museum experience, serving as a valuable resource for a diverse audience and contributing to cultural education and tourism in East Java.